Age and origin of a Cahokian wooden monument at the Mitchell site, Illinois, USA - Nicholas V. Kessler; Erin M. Benson; Timothy R. Pauketat; Jason D. Kirk; Matthew D. Therrell (PLoS ONE, 2025)
Cahokia was the first and largest precolonial city outside of Mesoamerica in what is now the United States. Monuments and exotic goods were central to public life at Cahokia, but no high-resolution timeline of monumental construction or long-distance material import exists for the site. Wooden marker posts, serving as both public monuments and exotic artifacts, offer ideal sources of evidence for documenting the chronology and spatial scale of Cahokian material networks and community histories. In this paper, we employ 14C dating of a cosmic event archived in tree-rings to determine that the largest known marker post in the Cahokia area, the Mitchell Log, was felled around 1124 CE. Sr isotope ratios of the wood rule out a local source, and suggest the tree was transported at least 180 kilometers. Together, the date, provenance, and context of the Mitchell Log (1) establish a historical datum for the peak influence of the Cahokia polity, (2) prompt new questions about the long-distance transport of thousands of other such marker posts, and (3) identify a significant event in the history of this precolonial phenomenon.